Language Learning Strategies for Foreign Language Learning and Teaching - Ikhsan, M Khairi (Universitas PGRI Sumatera Barat, 2015)
This paper is aimed at emphasizing the importance of language learning strategies in foreign language learning and teaching. It summarizes the background of language learning strategies, defines the concept of a language learning strategy, and outlines the taxonomy of language learning strategies proposed by several researchers. It also takes into account the teacher's role in strategy training and poses questions for further research on language learning strategies.